1993
DOI: 10.1104/pp.101.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Inducible Aerobic and Anaerobic Stress Proteins in the Echinochloa Complex and Rice

Abstract: Anaerobic stress resulted in a change i n the protein accumulation patterns in shoots of several Echinochloa (barnyard grass) species and Oryza safiva (1.) (rice) as resolved by two-dimensional gel electrophoresis. O f the six Echinochloa species investigated, E. phyllopogon (Stev.) KOSS, E. muricafa (Beauv.) Fern, E. oryzoides (Ard.) Fritsch Clayton, and E. crus-galli (1.) Beauv. are tolerant of anaerobiosis and germinate i n the absence of oxygen, as does rice.In contrast, E. crus-pavonis (H.B.K.) Schult and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 33 publications
3
44
0
1
Order By: Relevance
“…This shift in the pattern of protein synthesis has been observed in the roots of both monocotyledons (maize, Sachs et al [1980]; rice, Bertani et al [1981] and Mocquot et al [1981]; Echinochloa, Mujer et al [1993]) and dicotyledons (Arabidopsis, Dolferus et al [ 19851;soybean, Russell et al [1990]). The anaerobic protein profile of soybean is the simplest.…”
Section: Anaerobic Protein Synthesis In Tomato Rootsmentioning
confidence: 97%
“…This shift in the pattern of protein synthesis has been observed in the roots of both monocotyledons (maize, Sachs et al [1980]; rice, Bertani et al [1981] and Mocquot et al [1981]; Echinochloa, Mujer et al [1993]) and dicotyledons (Arabidopsis, Dolferus et al [ 19851;soybean, Russell et al [1990]). The anaerobic protein profile of soybean is the simplest.…”
Section: Anaerobic Protein Synthesis In Tomato Rootsmentioning
confidence: 97%
“…Anaerobic stress proteins have been characterized as glycolytic enzymes like alcohol dehydrogenase (Xie and Wu, 1989). It was reported that water-logging -intolerant Echinochloa species did not produce anaerobic proteins (Mujer et al 1993). Rivoal et al (1997) reported that ADH gene and other fermentative genes were induced by hypoxia and water-logging.…”
Section: Alcohol Dehydrogenase (Adh)mentioning
confidence: 99%
“…Rice coleoptiles survived more than 21 day under complete oxygen deprivation and their metabolic activity was high enough to allow RNA and protein synthesis (Cobb and Kennedy, 1987;Mujer et al, 1993;Umeda and Uchimiya, 1994). The tolerance of rice coleoptiles to oxygen defi ciency is related to the ability to maintain glycolytic activity leading to ATP production (Guglielminetti et al, 1995;Perata et al, 1997;Gibbs et al, 2000;Rahman et al, 2001).…”
mentioning
confidence: 99%